The Influence of Quality of Work Life, Organizational Culture, and Competence on Employee Performance with Motivation as a Mediating Variable in Dinas Pekerjaan Umum dan Perumahan Permukiman Kabupaten Situbondo - Dwi Cahya Yanottama; Purnamie Titisari; Diana Sulianti K Tobing (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of quality of work life (QWL), organizational culture, and competence on employee performance with motivation as a mediating variable in Dinas Pekerjaan Umum dan Perumahan Permukiman Kabupaten Situbondo. This study uses a quantitative approach with an explanatory method. The research sample consisted of 146 civil servants, which represented the entire population (saturated sample). Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through SmartPLS 3.0 software. The results showed that QWL, organizational culture, and competence significantly influence employee performance. Motivation also significantly influences employee performance, but only mediates the influence of competence on performance, and does not mediate the influence of QWL and organizational culture on performance.